Behavioural Factors Effect On Drift Demand For Tall Reinforced Concrete Buildings Subjected To Repeated Far-Field Earthquakes - Basir, Sabila Ahmad (2013)
Real earthquake event does not appear in single tremor but actually lead to appearance of several tremors consecutively. It is found that the sequences of ground motions have a significant effect on the response of reinforced concrete (RC) frames building. Previous research done mostly ignored the importance of the effect of repeated far-field earthquake (FFE) event. This thesis presents a seismic response evaluation of two tall building models in term of drift demand subjected to single and repeated FFE records at various behavioural factors, qo using linear and nonlinear analysis. Analysis was performed in bi-directional horizontal components of the building by subjecting the RC structural model to FFE in single, double and triple of 20 strong earthquake events. The performances of both tall building models were evaluated based on seismic action towards the stiffness and strength of the building model. From all results obtained, drift demand drastically increases with 18m different in height between top floor of twelve (N=12) RC storey and 17th floor of eighteen (N=18) RC storey building models with same structural element properties.